Implementing knowledge management: a framework for Telekom Malaysia / Haznita Abdul Halim - Abdul Halim, Haznita (2002)
Telekom Malaysia Berhad is one of the leaders in the telecommunications industry in Malaysia. In order to achieve its vision to be a world class telecommunications company, the company can not ignore the global trend which focuses on developing and implementing knowledge management programs, so that it can leverage on its knowledge resources. Like many large organizations, Telekom experiences many knowledge related problems. However, so far, there has been no study on the implementation of knowledge management at Telekom Malaysia. To address this opportunity, a framework for the implementation of knowledge management at Telekom Malaysia is proposed, in an attempt to resolve the knowledge related problems at the company.